High-current-density Rutherford MgB2 cable sheathed by CuNi30 alloy. (22nd September 2022) - Kováč, P; Kopera, L; Berek, D; Hain, M; Melišek, T; Hušek, I; Kováč, J; Búran, M
Abstract: A Rutherford-type MgB2 cable has been fabricated from 12 six-core strands prepared by an internal magnesium diffusion (IMD) process with a resistive CuNi30 outer sheath. The uniformity of individual strands of diameter 0.448 mm prior to and after additional densification by rolling was studied by x-ray micro-tomography. The engineering current densities of the cable samples were measured at 4.2 K and external magnetic fields between 4.0 T and 8.0 T and compared with available published data. The presented Rutherford cable has the highest engineering current density with J e = 10 4 A cm 2 measured in an external magnetic field of 5.73 T. The bending tolerance of the cable shows a critical diameter of 60 mm and less gradual critical current degradation in comparison to similar cables fabricated from single-core strands. The AC loss measurements of the present cable show lower coupling losses in comparison to monolithic multicore IMD conductors. The obtained results are promising for high-current-density and low-AC-loss MgB2 superconducting cables that are suitable especially for motors and generators.